Engineering and economics of the hazardous wastes in Colombia: the need for a circular economy model (2019)
This document collects and organizes data on not only the generation and current situation of hazardous wastes from Colombia, but also in a Latin American and global context. These materials were studied regarding the current economic model, regulations and implications in society. In addition, the numbers are presented from different reports from waste generating companies and, more importantly, from the data officers of the National Institute of Hydrology, Meteorology and Environmental Studies (IDEAM). We also analyzed the activities that contribute most to these wastes and their relationship with various aspects, such as gross domestic product and Oil production in different regions of the country. Therefore, the main objective of this project is to analyze the state of hazardous waste in Colombia in quantitative form, in order to begin to give real solutions towards the use, research and commercialization of derivative products that help reduce their negative effect on the environment.